If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 4 = -1y Reorder the terms: 4 + -1x = -1y Solving 4 + -1x = -1y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = -4 + -1y Combine like terms: 4 + -4 = 0 0 + -1x = -4 + -1y -1x = -4 + -1y Divide each side by '-1'. x = 4 + y Simplifying x = 4 + y
| 2x+15x^2=24 | | 7.6-0.7h+1.2-1.3h=24-2.0h-6.7 | | 6.9x-3.6=24.0 | | 6y^2=-7-2 | | 8/3x-21/2 | | 2x+15x^2=32 | | 5x5/5/7 | | 128=8-4e | | 45x+27= | | 2x+15x^2=35 | | x^3+5x^2-4x-2=0 | | 25=-5y-6x | | -6w^2+150w=0 | | 5(2x-17)=10x-85 | | 5x+x^2=y | | -13+3x+4+-5x=15 | | 0.06x-0.10(x-2)=0.02(8) | | 36+7-25+7= | | 4x-15/3=7 | | -2(7x-4)+3(5x-4)-3=7-3 | | 28+p=39 | | 10g+10=29g | | 17.40=1.5n | | 3y=8-2x | | 3x+4(x-8)= | | -7r+14=-71 | | -4(3x+6y)+12x+4y= | | 12x+.50y=112 | | 3cotx+3=8 | | 0=-15-3y+2x | | 25=x+2x+3x+1 | | z^2-6z+9+2i=0 |